Awareness on the cost-effective treatment modalities for the management of pain among weavers in Kanchipuram, Tamilnadu (Journal of Pharmaceutical Negative Results, 2022)
Background: Kanchipuram is one of the biggest production centres of pure silk handlooms where no entry of power looms is being tolerated nor an introduction of any new techniques of production is readily accepted by the most quality-conscious weavers who are more concerned with the stable fineness of the texture of their handloom fabrics. Literature suggests that Indian handloom weavers have high prevalence of pain.Aim: To educate the weavers about the cost effective treatment modalities for the management of pain. Evaluation of degree of pain and various treatment modalities obtained by the weavers.Methods: Various treatment modalities were evaluated using a performed questionnaire. Their degree of pain was assessed using Brief pain inventory scale.Results: The present study showed that around 32.80% of the weavers within the age group of 25-50 years were affected by severe pain. And 54% of weavers were under the AYUSH medications and also 36% of weavers preferred NSAIDs, among them Diclofenac and Paracetamol are the most commonly prescribed drugs.Conclusion: Our present study would have helped the weavers to obtain the cost effective and alternate treatment modalities for management of pain.